Virulence and Evolution of West Nile Virus, Australia, 1960–2012 - Prow, Natalie A. (Emerg Infect Dis, 2016)
Worldwide, West Nile virus (WNV) causes encephalitis in humans, horses, and birds. The Kunjin strain of WNV (WNV(KUN)) is endemic to northern Australia, but infections are usually asymptomatic. In 2011, an unprecedented outbreak of equine encephalitis occurred in southeastern Australia; most of the ≈900 reported cases were attributed to a newly emerged WNV(KUN) strain. To investigate the origins of this virus, we performed genetic analysis and in vitro and in vivo studies of 13 WNV(KUN) isolates collected from different regions of Australia during 1960–2012. Although no disease was recorded for 1984, 2000, or 2012, isolates collected during those years (from Victoria, Queensland, and New South Wales, respectively) exhibited levels of virulence in mice similar to that of the 2011 outbreak strain. Thus, virulent strains of WNV(KUN) have circulated in Australia for >30 years, and the first extensive outbreak of equine disease in Australia probably resulted from a combination of specific ecologic and epidemiologic conditions.